Empirical Analysis of the Relationship between Renewable Energy Consumption and Economic Growth Based on the Grey Markov Model - Chao Liu (Journal of Mathematics)
According to the global renewable energy attraction index, countries (regions) are selected as the analysis samples, and then the function model is improved. Considered as independent input factors into the function, the sample countries and the data are analyzed for stationarity and cointegration relationship test. With the excessive use of nonrenewable energy and the frequent occurrence of nuclear safety problems, it is imperative to develop renewable energy under the background that governments all over the world advocate energy conservation and emission reduction. By formulating active renewable energy industrial policies, governments and enterprises can not only enable the government to achieve the goal of energy conservation and emission reduction but also promote economic development to a certain extent. 34 countries (regions) were selected as analysis samples, and then the production function model was improved. Renewable energy and nonrenewable energy were considered as independent input factors into the Cobb-Douglas function, and the panel data model was established by using the economic data of sample countries from 1994 to 2014.